The Urgency of the Scientific Method Based on Akidah Akhlak Learning according to Imam Al-Ghazali's Perspective on Increasing Student Faith - Amelia Khoirunisa; Fachril Achmad Aziz; Moh. Faizin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Abstract: The Urgency of the Scientific Method Based on Akidah Akhlak Learning according to Imam Al-Ghazali's Perspective on Increasing Student FaithThe religious life and faith of students in the context of aqidah akhlak learning are very important. This study aims to explain the urgency of the scientific method in increasing students' faith with a focus on Imam Al-Ghazali's perspective. This research uses the library research method. The data analysis used in this research is a literature review. The results explain Al-Ghazali's perspective on aqidah, the scientific method can help students develop a deeper understanding of aqidah through a rational and objective approach. The urgency of the scientific method in improving faith includes increasing understanding of religion, overcoming doubts, improving the quality of research, and improving the quality of teaching. The conclusion shows that the understanding of aqidah from the perspective of Imam Al-Ghazali emphasizes the importance of a correct understanding of aqidah as the foundation of a Muslim's life. The importance of the scientific method in faith enhancement lies in its ability to increase understanding of religion, overcome doubts and improve the quality of teaching. Abstract: Urgensi Metode Ilmiah dalam Peningkatan Keimanan Mahasiswa pada Pembelajaran Aqidah: Tinjauan dalam Perspektif Imam Al-Ghazali.Kehidupan keagamaan dan keimanan mahasiswa dalam konteks pembelajaran aqidah merupakan hal yang sangat penting. Penelitian ini bertujuan untuk menjelaskan urgensi metode ilmiah dalam meningkatkan keimanan mahasiswa dengan fokus pada perspektif Imam Al-Ghazali. Penelitian ini menggunakan metode library research. Analisis data yang digunakan dalam penelitian ini adalah literatur review. Hasil penelitian menerangkan perspektif Al-Ghazali mengenai aqidah, metode ilmiah dapat membantu mahasiswa mengembangkan pemahaman yang lebih mendalam terhadap aqidah melalui pendekatan rasional dan objektif. Urgensi metode ilmiah dalam meningkatkan keimanan meliputi meningkatkan pemahaman tentang agama, mengatasi keraguan, meningkatkan kualitas penelitian, serta peningkatkan kualitas pengajaran. Kesimpulan menunjukkan bahwa pemahaman aqidah dari perspektif Imam Al-Ghazali menekankan pentingnya pemahaman yang benar tentang aqidah sebagai landasan hidup seorang muslim. Urgensi metode ilmiah dalam peningkatan keimanan terletak pada kemampuannya untuk meningkatkan pemahaman tentang agama, mengatasi keraguan dan meningkatkan kualitas pengajaran.